International Human Rights through Queer Theory: A Discursive Analysis of the Russian, Lithuanian, and Kyrgyz LGBTQ+ Lived Experience within the Global Paradigm - Youssef, Mariem (AUC Knowledge Fountain, 2023)
This thesis attempts to shed light on the subordination of international human rights law to that of the paradigm of international relations through asserting the existence of US Empire i.e., that emulates historical empires, British and French, which aims to emancipate subjugated minorities, formerly women and presently LGBTQ+ individuals from their national oppressive regimes. This is achieved through a discussion of pervious literature that discusses queer theory with a special focus on Russia, Lithuania, and Kyrgyzstan as the main case studies. While the overt intentionality of the “empire” is to protect LGBTQ+ individuals through perpetuating the prototype of the “International Gay”, this actually further compounds the problem of LGBTQ+ individuals who find themselves unable to fit within the normative structure of the “International Gay” and being further oppressed by their respective regimes due to the mounting international pressure, such as in Russia, Lithuania, and Kyrgyzstan. This research argues that the discourses mobilized by activists is a 'queer' discourse that both uses and opposes the symbols, categorizations, and language of the international LGBTQ+ rights regime. At the same time uses and opposes nationalist symbols, categorizations, and language of their state governments, responsible for their oppression and repression. In addition, it draws from queer theory to help explain this dynamic.